FACTORS ASSOCIATED WITH FEAR OF CHILD BIRTH AMONG PRIMARY GRAVIDA WOMEN IN PESHAWAR (The Research of Medical Science Review, 2025)
Introduction: Childbearing is one of the most common physiological phenomena in a women’s life which is closely associated with fear and anxiety. The whole process of gestation and childbirth has significant physical and emotional effects which may produce certain risks and complications for both mother and child. Therefore, recently mother and child health care has been focusing on childbirth-related complications and risks for both mother and child. Statistics and prevalence regarding fear of childbirth among primary gravida women vary around the globe. Objectives: To determine the factors associated with fear of childbirth among primary gravida women in Peshawar. Methodology: A cross-sectional study was conducted in the Gynecology ward and labor Rooms of Lady Reading Hospital Peshawar Khyber Pakhtunkhwa. Data was collected from overall, 360 participants using a validated questionnaire. Data from all included participants were collected following the consecutive sampling technique. Data were analyzed using SPSS version 24. Results: Data was collected from 360 participants, the mean age of the participants was 27.42 years. The majority (34%) of the participants were illiterate. Nearly half (47.2%) participants have reported family income as inadequate. The majority (70.6%) of the primary gravida mothers were experiencing severe fear of childbirth, 17.8% primary gravida mothers were experiencing moderate fear while 11.7% mothers were experiencing mild fear. Age (P= 0.018), Education (P=000), residence (P=0.000), income (P=0.000), and Miscarriage (P=0.01) of the primary gravida women significantly associated with fear. Conclusion: The findings of the study revealed that the women experiencing fear of childbirth. Certain factors which contribute to fear were pain, episiotomy, a problem during labor and delivery, unfriendly staff during labor and delivery, reproductive health problems, and cesarean section prevalent among primary gravida women. Age, Education, residence, income, and Miscarriage of the primary gravida women are significantly associated with fear in primary gravida women.